Anesthetic Management of Humerus Fracture with Multiple Trauma and Pneumothorax - Gyawali, Nirmal Kumar; Sharma, Prastuti (Journal of Karnali Academy of Health Sciences, 2019)
Background: Trauma is a significant health problem and a leading cause of death in all age group. Methodology: In this study we describe anesthetic management of poly trauma with pneumthorax in a 55 years old male with humerus fracture. Result: Patient with multiple trauma with pneumothorax was safely anaesthesized with regional anesthesia. This procedure also prevented progression of pneumothorax to tension pneumothorax. Conclusion: Regional anesthesia is a safe alternative of general anesthesia in case of patient with pneumothorax for the upper limb surgery.